2015
DOI: 10.7727/wimj.2014.228
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Workplace Stigma and Discrimination among People Living With HIV/AIDS Attending Antiretroviral Clinics in Health Institutions in Enugu, South East Nigeria

Abstract: The prevalence of stigma and discrimination in workplaces is high. Efforts should be made by agencies to reduce such social problems in the workplace since they can affect overall management and productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Stories of Dagie and Mafene demonstrate and represent several ways in which fears of death present daily in the lives of these youth, despite the assurance that with ART they can live longer. Just like extant literature [60,61], our findings relate this fear to the historical prognosis of HIV during the pre-ART era. Therefore, sensitization and reassurance, is necessary to dispel such historical views.…”
Section: Plos Onesupporting
confidence: 69%
“…Stories of Dagie and Mafene demonstrate and represent several ways in which fears of death present daily in the lives of these youth, despite the assurance that with ART they can live longer. Just like extant literature [60,61], our findings relate this fear to the historical prognosis of HIV during the pre-ART era. Therefore, sensitization and reassurance, is necessary to dispel such historical views.…”
Section: Plos Onesupporting
confidence: 69%
“…Finally, health related stigma by co-workers could result in social exclusion, which led to a diminished well-being at work of people with disabilities and problems in maintaining a job. Studies about both physical and mental disabilities reported social exclusion by co-workers [37,48,60,66,77,[85][86][87][88]. However, the risk of social exclusion seemed to be especially prominent in case of workers with contagious diseases like HPB/C or HIV due to the concerns of co-workers about possible transmission.…”
Section: Co-workersmentioning
confidence: 99%
“…Ways in which health related stigma affected sustainable employment and well-being at work of people with disabilities Harassment and bullying negatively affected someone's wellbeing at work and chance to maintain a job by making them upset and lowering their self-esteem, this could lead them to resign[37,65,66,70,74,75,[81][82][83][84] Social exclusion led to a diminished well-being at work and was barrier in maintaining work, it could lead to strained relationships and a loss of motivation to perform a job[37,48,60,66,77,[85][86][87][88][89][90] …”
mentioning
confidence: 99%
“…We identified several studies that addressed stigmatization in the workplace. However, we only found studies that addressed specific problems and stigmatizing attitudes against specific populations, such as cancer patients (Stergiou‐Kita et al., 2016) and HIV positive individuals in the workplace (Aguwa et al., 2016). Due to the gap in the Turkish literature about workplace stigmatization, we first aimed to comprehend the scope of the problem.…”
Section: Methodsmentioning
confidence: 99%